THE INFLUENCE OF KIAI SOLEH DARAT'S TAFSIR FAIDH AR-RAHMAN ON KARTINI'S THOUGHT 1889-1902 - Naufal Hibban Firdaus; Muhammad Mufti Najmul Umam; Agus Mulyana (Vol. 3 No. 2 (2025): Special Issue: Cultural Resilience and Digital Literacy for a Diverse Society, 2025)
Kartini was a well-known figure in the early 20th century for her thoughts on women's emancipation and liberation from Javanese feudal customs. These thoughts emerged due to intellectual activities in the form of correspondence with her Dutch friends. Kartini was initially skeptical of Islam, which she thought supported Javanese feudal customs. This happened because Kartini's correspondence friends influenced her. However, some time later there was a cleric from Semarang who inspired Kartini, namely Kiai Soleh Darat, Kartini felt a light when listening to explanations about the Qur'an that she could not previously get. Finally there was a change in Kartini's view of Islam and women's emancipation that she had discussed with her correspondence friend, this change was the influence of Kiai Soleh Darat's tafsir Faidh Ar-Rahman. This research was made to see how Kiai Soleh Darat as an environmental reality can influence someone with the tafsir Faidh Ar-Rahman as a source of teachings and Islamic values used as a container. The purpose of this research is to dissect Kartini's thoughts related to the above aspects influenced by Kiai Soleh Darat's tafsir Faidh Ar-Rahman. The theoretical approach used is critical discourse analysis theory and social construction theory to dissect Kartini's letters and the social reality that existed at that time. Then, the method used is a qualitative method with a focus on literature review of Kartini's letters and the book of tafsir Faidh Ar-Rahman supported by other sources related to the research. The results of this study show that there are changes in Kartini's thoughts about Islam, women's emancipation, and views on Javanese feudal customs as seen from her letters before and after reading Kiai Soleh Darat's tafsir Faidh Ar-Rahman.